THE EFFECT OF CREATIVITY AND LOYALTY ON EMPLOYEE PERFORMANCE IN PT. TRIBUN MEDAN DAILY - Ilham Sonata; Syamsul Effendi; Rizky Ananda Hasibuan (SEAN Institute, 2022)
Tribun Medan is one of the local newspaper network companies in Kompas Gramedia that provides useful information or knowledge for the community. The purpose of this study was to determine the effect of creativity on employee performance, the effect of loyalty on employee performance and the influence of creativity and loyalty on employee performance at PT. Tribun Medan Daily. The population in this study amounted to 114 respondents, the determination of the sample in this study using the Slovin formula and the sample obtained was 53 respondents. The data obtained in this study are primary data obtained from questionnaires. The data analysis technique used is descriptive analysis and multiple linear regression analysis which will then be processed using the SPSS Version 23 application. Based on the research results, it is known that Creativity and Loyalty have a significant positive effect on Employee Performance. This can be seen from the results of the F-test where F-count is 59.493 with a significance level of 0.000. Based on the results of the data if the value of the coefficient of determination R2 is 0.704 which indicates that 70.4% of employee performance at PT. Daily Tribune Medan in the influence of Creativity and Loyalty while the rest is influenced by other factors in this study.